Implications of adopting new WHO guidelines for antiretroviral therapy initiation in Ethiopia - Elke Konings; Yirga Ambaw; Katherine Dilley; Peter Gichangi; Tesfaye Arega; Bud Crandall (The World Health Organization, 2012)
OBJECTIVE: To assess the implications of implementing the World Health Organization (WHO) 2010 guidelines for antiretroviral therapy (ART) initiation in adults and adolescents with human immunodeficiency virus (HIV) infection, which recommend initiating ART at a CD4+ T lymphocyte (CD4+) threshold of < 350 cells/mm³ instead of < 200 cells/mm³, which was the earlier threshold. METHODS: Between April and May 2010, CD4+ test results were collected for all HIV-infected patients recorded in the pre-ART and ART registers of 19 high-patient-load health centres in Addis Ababa, Ethiopia, and the regions of Amhara, Oromia, SNNPR (Southern Nations, Nationalities and People's Region) and Tigray. At 12 centres patient records were independently reviewed to assess data accuracy. To estimate the total number of patients who would need ART at health centres if Ethiopia adopted the new WHO guidelines, the number of patients needing ART based on current guidelines were added to the number of asymptomatic patients enrolled in pre-ART with a CD4+ count > 200 but < 350 cells/mm³ FINDINGS: Adoption of the new WHO guidelines would increase the total number of patients on ART in the 19 health centres in Ethiopia by about 30%: from 3583 to 4640. CONCLUSION: The shift in the CD4+ threshold for ART initiation will substantially increase the demand for ART in Ethiopia. Since under the current systems only 60% of Ethiopia's patients in need of ART are receiving the medications, scaling up ART programmes to accommodate the increased demand for drugs will not be possible unless government funding and support increase concurrently.